The Effect of Single-port Transvesical Laparoscopic Radical Prostatectomy on Erectile Function and Urinary Continence Compared to Intrafascial Endoscopic Extraperitoneal Radical Prostatectomy - Yang, Yi; Hou, Guoliang; Mei, Hongbing; Zhang, Xintao; Han, Xiaohong; Pang, Jun; Gao, Xin (Urology Journal, 2020)
Purpose: To compare the erectile function and urinary continence of patients after single-port transvesical laparoscopic radical prostatectomy (STLRP) with intrafascial endoscopic extraperitoneal radical prostatectomy (IEERP). Materials and Methods: Patients treated with STLRP (35) or IEERP (52) were recruited from September 2013 to June 2017. At baseline preoperatively and 2-year follow-up postoperatively, sex and continence assessments were performed by International Index of Erectile Function-6 (IIEF-6) and daily pads, respectively. Results: The sexual function at 3 months after RP declined obviously. 71.4% (STLRP) and 38.5% (IEERP) patients recovered potency at 6 months postoperatively (P < .01). 82.9% (STLRP) and 59.6% (IEERP) patients recovered potency at 2 years postoperatively (P < .05). 97.1% (STLRP) and 75.0% (IEERP) patients recovered continence (0 pad/day) at 3 months postoperatively (P < .01). Continence achieved 100.0% at 2 years after RP in both groups. Conclusion: Patients receiving STLRP may obtain better and faster postoperative functional recovery than the ones receiving IEERP. As an exploratory research, STLRP may be another effective treatment for organ-confined prostate cancer.